2016
DOI: 10.1039/c6ra11313c
|View full text |Cite
|
Sign up to set email alerts
|

Molecules with O-acetyl group protect protein glycation by acetylating lysine residues

Abstract: Pharmaceutical intervention for reduction of advanced glycation products (AGEs) is considered as a therapeutic strategy to attenuate the pathogenesis of diabetes. Many molecules have been reported to possess antiglycation activity, one such example is acetylsalicylic acid (Aspirin). It protects proteins from glycation by acetylating the lysine residues. Therefore, in this study we have synthesized and screened molecules containing free N-, O-acetyl and acetophenone group. All the selected molecules in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Previous studies have indicated the neuroprotective effects of AAP stemming from its effect on the inflammatory pathways in lipopolysaccharide-induced cognitive impairment in mice (29). In addition, in the structure of DAPPD, the additional acetamide functionality could exhibit an improved enzymatic and metabolic stability under physiologically relevant conditions (30,31). Taken together, DAPPD could be an ideal candidate as an antineuroinflammatory compound in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated the neuroprotective effects of AAP stemming from its effect on the inflammatory pathways in lipopolysaccharide-induced cognitive impairment in mice (29). In addition, in the structure of DAPPD, the additional acetamide functionality could exhibit an improved enzymatic and metabolic stability under physiologically relevant conditions (30,31). Taken together, DAPPD could be an ideal candidate as an antineuroinflammatory compound in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Such compounds can be destroyed after enzymatic hydrolysis and removed by SPE afterwards. Currently, several commercial products, delivering reliable and reproducible results are available: anionic acid labile surfactant (AALS) from Progenta [ 53 , 175 ], acid labile RapiGest SF Surfactant from Waters Corporation [ 184 , 185 ]. Additionally, acid cleavable detergents ProteaseMax (Promega) [ 186 ], PPS Silent Surfactant (Expedeon) [ 187 ], and Invitrosol (Invitrogen) [ 188 ] might be used in analysis of post-translationally modified proteins.…”
Section: Part 1 Probing the Structure Of Glycated Proteins By Masmentioning
confidence: 99%
“…C2, on the other hand, has an acetyl group bound to the amino group of lysine, resulting in an amide group, which is less reactive under physiological conditions than the original primary amine (Hacker et al., 2017; Vannuruswamy et al., 2016; Zhang et al., 2019). Consequently, the presence of the acetyl group in the linker can explain the apparent disagreement between PPB and lipophilicity of the gallium complexes.…”
Section: Resultsmentioning
confidence: 99%